Evaluation of microbial cultures for the preparation of kombucha (Research, Society and Development, 2021)
Kombucha is a drink obtained by the fermentation of green and/or black tea added to a source of sugar, subjected to a symbiotic fermentation between yeasts and bacteria present in aggregated botanicals or from previously selected and/or stored culture. The growing popularity of kombucha is due to its antioxidant properties, B vitamins and organic acids, which have been shown to be beneficial to health. In this work Kombucha formulations were produced with 3 different cultures of microorganisms. The tea extract was prepared with herbs and spices found in the local market and the source of sugar was honey. The formulations were submitted to fermentation for 11 days. Physicochemical analyzes were performed, before and after fermentation. After fermentation, the drink was carbonated and divided into two groups, pasteurized and in natura. After 8 days the samples were submitted to a sensory analysis. The results with industrial yeast and vinegar mother, native yeast and vinegar mother and mixed culture of bacteria and yeast (vinegar mother culture) provided distinct flavors and aromas, and the treatment with industrial + native yeast had metabolization rates of higher sugars with consequent greater formation of alcohol and reduction of sugars, but less formation of acids. In the sensory evaluation, the mother culture was more accepted. The thermal treatment affected the formulations sensorially. The isolated mother culture obtained the best scores when in natura.